Disrupción endocrina e imposex - Chacón, Óscar; Cuevas, Fabrizio; De La Fuente, Christian; Díaz, Fabián; Huaquín, Laura (Avances en Ciencias Veterinarias, 2007)
From the injurious effects generate by the pollutants, Endocrine Disruption (ED) constitute one of the worrying cases, since it affects directly the individuals exposed to the substances that act like disruptors, as indirectly causing effects in the trophic chain, and in the environment in general. Inside them, we will approach in this review a type of endocrine disruption called Imposex, which affects diverse species of marine gasteropods, with environmental consequences, economic and possible effects in mammals included humans.